Effect of processed spent bleaching earth and kenaf fiber towards heat of hydration and strength of foamed concrete - Muhammad Zulkarnain, Hamdan (2019)
Pozzolanic materials such as Processed Spent Bleaching Earth (PSBE) have been widely used as a partial cement replacement material in concrete construction due to its pozzolanic properties. PSBE is solid waste generated from the bleaching process in the palm oil industry by using solvent extraction of crude oil. In this study, the effects of PSBE and kenaf fiber on workability, the heat of hydration and compressive strength of foamed concrete investigated. These are three mixtures that have prepared, namely foamed concrete (FC), 30% PSBE (PFC) and 30% PSBE + kenaf fiber (PKC). All the mixtures have been tested with the workability test first. From the experiment, it found that PKC has the lowest flowability, which is about 8% lower compared with FC. For the heat of hydration test, the results have proved that PKC produced foamed concrete that has the lowest peak temperature, which is 7% and 25% lower than FC for 150x150x150mm and 300x300x300mm cube sizes. Other than that, it observed that PKC consumed the longest time taken to achieve its peak temperature compared with FC by 30% and 45% longer for 150x150x150mm and 300x300x300mm cube sizes. Lastly, for the compression test, it shown that PFC has the highest compressive strength for 7, 28 and 60 days compared to others. In a nutshell, based on observations and results obtained by this study, it can be concluded that the presence of PSBE that act as partial cement replacement is a beneficial, especially for the production of foamed concrete.